The Role of School Principals in Improving the Quality of Education through School-Based Management Concepts - Jhanatri, Erinda; Ahyani, Nur; Mulyadi, Mulyadi (Journal of Social Work and Science Education, 2024)
This research aims to determine and describe the role of school principals in planning, organizing, moving, supervising, and evaluating the quality of education through the concept of school-based management at SMP Negeri 5 Prabumulih city. This research was carried out at SMP Negeri 5 Prabumulih City, with a total of 8 informants. Data collection techniques through observation, interviews, and documentation studies. The results of this research are that the role of the school principal in planning, organizing, moving, supervising, and evaluating to improve the quality of education through the concept of school-based management has been implemented well.